2020
DOI: 10.1111/jgs.16667
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dementia Care Co‐Management on Acute Care, Hospice, and Long‐Term Care Utilization

Abstract: See related editorial by Callahan et al. in this issue. BACKGROUND/OBJECTIVES: Although nurse practitioner dementia care co-management has been shown to reduce total cost of care for fee-for-service (FFS) Medicare beneficiaries, the reasons for cost savings are unknown. To further understand the impact of dementia co-management on costs, we examined acute care utilization, long-term care admissions, and hospice use of program enrollees as compared with persons with dementia not in the program using FFS and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…The researchers also found, however, that other types of single interventions, including exercise, psychosocial support and health professional training, and multifactorial assessment and treatment had no effect on nursing home admissions 654 . In a retrospective case‐controlled study of a dementia care program that used nurse practitioners and physicians to co‐manage individuals with dementia, individuals enrolled in the program had 9.4 fewer emergency department visits and 160.1 fewer hospital days per 1,000 participants per quarter, 656 and were less likely to have a long‐term care nursing home admission over three years, 657 although there was no difference in hospital admissions 656 . Additionally, the program saved $284 per person per quarter in 2013 dollars ($346 in 2020 dollars) after taking into account program costs that included clinician and staff time, payments to community‐based organizations, supplies and other costs 657 .…”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…The researchers also found, however, that other types of single interventions, including exercise, psychosocial support and health professional training, and multifactorial assessment and treatment had no effect on nursing home admissions 654 . In a retrospective case‐controlled study of a dementia care program that used nurse practitioners and physicians to co‐manage individuals with dementia, individuals enrolled in the program had 9.4 fewer emergency department visits and 160.1 fewer hospital days per 1,000 participants per quarter, 656 and were less likely to have a long‐term care nursing home admission over three years, 657 although there was no difference in hospital admissions 656 . Additionally, the program saved $284 per person per quarter in 2013 dollars ($346 in 2020 dollars) after taking into account program costs that included clinician and staff time, payments to community‐based organizations, supplies and other costs 657 .…”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…In the context of evaluating a comprehensive dementia care program [9] that has shown clinical [10], utilization [11], and cost benefits [12], we interviewed and surveyed a subset of caregivers of persons in the program who did not demonstrate any benefit on clinical outcomes, including validated scales assessing dementia-related neuropsychiatric symptoms and caregiver strain and depression [10]. When examining characteristics of caregivers interviewed, we found that they commonly reported feeling "completely overwhelmed," [13] an item from the Modified Caregiver Strain Index [14], which was administered to all program participants at entry into the program.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Specialized care for older adults living with dementia, such as a dementia care program, has demonstrated reductions in acute health service use and long-stay transitions to a nursing home. 8,10 Assisted living facilities are referred to as retirement homes in the province of Ontario, Canada. Similar to assisted living facilities in the United States that are regulated at the statelevel, 11 retirement homes are regulated by an independent, not-for-profit regulator (i.e., Retirement Homes Regulatory Authority [RHRA]) in Ontario since 2011.…”
Section: Introductionmentioning
confidence: 99%
“…69 Specialized care for older adults living with dementia, such as a dementia care program, has demonstrated reductions in acute health service use and long-stay transitions to a nursing home. 8,10…”
Section: Introductionmentioning
confidence: 99%